PROMOTING VOLUNTEERING AMONG OLDER ADULTS IN HONG KONG: AN INTERVENTION STUDY. (16th November 2018) - Jiang, D; Warner, L; Chong, A; Li, T; Wolff, J; Chou, K
Abstract: Volunteering is consistently found to be positively associated with mental, physical, and cognitive health in older adulthood. However, the volunteering participation rate of older adults in Hong Kong is much lower than in western countries, such as U.S. and Australia. Few studies have examined whether interventions would be effective in motivating older adults to volunteer in Hong Kong. To fill this gap, we conducted a randomized control trail to examine the impact of a theory-based social-cognitive intervention on volunteering. 264 community-dwelling older adults in Hong Kong (Mage = 69.95 years, SDage = 6.90 years, female 81.06%) were randomly assigned into either an intervention group or an active control group. Participants in the intervention group received four weekly one-hour face-to-face volunteering intervention sessions. Based on the framework of Health Action Process Approach (HAPA), the volunteering intervention aimed at increasing positive attitudes and self-efficacy towards volunteering, and at helping older adults to establish personal goals and plans for future volunteering. Participants in the active control group received a parallel intervention targeting physical activity. Self-reported monthly volunteering minutes were measured at baseline, six weeks, three months, and six months after the intervention. We found that monthly volunteering minutes increased more significantly among participants in the intervention group than their counterparts in the active control group at six weeks, three months, and six months follow-up assessments. Action planning mediated the link between intervention condition and volunteering minutes. These findings demonstrate the effectiveness of the intervention on volunteering behaviour in older adults in Hong Kong.